1997
DOI: 10.3109/00016349709047789
|View full text |Cite
|
Sign up to set email alerts
|

A population study of urinary incontinence and nocturia among women aged 20‐59 years

Abstract: Urinary incontinence and nocturia affect well-being in a negative way. Well-being and wish for treatment correlate to frequency of incontinence but not to type of incontinence. Most women with UI accept it, only about a quarter of incontinent women, or 6-7% of all women in the studied age group, want treatment. Treatment of female urinary incontinence in primary health care is successful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
115
6
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(132 citation statements)
references
References 15 publications
9
115
6
2
Order By: Relevance
“…Several studies have reported on the impairment in sexual lives as a result of urinary symptoms. 1,[21][22][23][24][25] Some reports have found that patients with urinary symptoms due to a combination of GSI and DI experience more sexual dissatisfaction than patients with GSI alone. 1,22,23 However, there is some debates as to whether urinary leakage occurs more commonly in DI than in GSI.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported on the impairment in sexual lives as a result of urinary symptoms. 1,[21][22][23][24][25] Some reports have found that patients with urinary symptoms due to a combination of GSI and DI experience more sexual dissatisfaction than patients with GSI alone. 1,22,23 However, there is some debates as to whether urinary leakage occurs more commonly in DI than in GSI.…”
Section: Discussionmentioning
confidence: 99%
“…Studies among younger populations in Austria and Sweden gave lower prevalence rates. Of Swedish women aged 20-59 years 6.5% had nocturia [12]. Austrian women aged ≥ 20 years had a prevalence rate of 12%, while 11% of the men in this population had nocturia [1].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, and as testament to the prevalence of this issue, 25 -28% of women between the ages of 20 and 59 are affected by continence issues (Samuelsson et al, 1997;Hägglund and Wadensten, 2007;Hannestad et al, 2000). As a result, people managing continence concerns may experience feelings of shame, social exclusion and reluctance to venture outside into unknown areas of the built environment (Verhoef et al, 2005;Hägglund and Wadensten, 2007).…”
Section: Case Study 3: the Need For Accessible Toilet Facilitiesmentioning
confidence: 99%